2020
DOI: 10.1016/j.jmoldx.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Acoustofluidic Salivary Exosome Isolation

Abstract: Previous efforts to evaluate the detection of human papilloma viral (HPV) DNA in whole saliva as a diagnostic measure for HPV-associated oropharyngeal cancer (HPV-OPC) have not shown sufficient clinical performance. We hypothesize that salivary exosomes are packaged with HPV-associated biomarkers, and efficient enrichment of salivary exosomes through isolation can enhance diagnostic and prognostic performance for HPV-OPC. In this study, an acoustofluidic (the fusion of acoustics and microfluidics) platform was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 36 publications
1
68
0
Order By: Relevance
“…Salivaderived exosomes are separated and purified based on the size using a newly developed acoustic fluid platform, which combined acoustics with microfluidic technology. The average yield of small RNA in exosomes detected by RT-ddPCR using this technique is 15 times that of differential centrifugation, and studies have found that harvesting exosomes by this technique is beneficial for downstream analysis 62 . In addition, separation techniques such as Tangential Flow Filtration, 63 Flow fieldflow fractionation (FIFFF) 64 and Deterministic lateral displacement array 65 also have good enrichment potential.…”
Section: Other Isolation Techniquesmentioning
confidence: 99%
“…Salivaderived exosomes are separated and purified based on the size using a newly developed acoustic fluid platform, which combined acoustics with microfluidic technology. The average yield of small RNA in exosomes detected by RT-ddPCR using this technique is 15 times that of differential centrifugation, and studies have found that harvesting exosomes by this technique is beneficial for downstream analysis 62 . In addition, separation techniques such as Tangential Flow Filtration, 63 Flow fieldflow fractionation (FIFFF) 64 and Deterministic lateral displacement array 65 also have good enrichment potential.…”
Section: Other Isolation Techniquesmentioning
confidence: 99%
“…While the problem of specimen has been addressed, we underlined the utility of technical adaptations of classic methods, such as ddPCR or fluorescent-based detection methods as they either provide quicker analysis [127] or feasibility for high-throughput screening [107] and require a smaller screening volume. If these techniques are further improved and the advantages combined, they might make implementing EV isolation in clinical settings possible.…”
Section: Resultsmentioning
confidence: 99%
“…Pancreatic juice can be very viscous when patients suffer from intraductal papillary mucinous neoplasm due to high mucin concentration, which makes exosome isolation difficult [88]. High viscosity is also a problem reported for whole saliva [107]. These are just a few examples of problems that have to be overcome.…”
Section: Characterization and Importance Of Extracellular Vesicle (Evmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes from saliva were isolated using an acoustofluidic platform and investigated for small RNA and DNA content using droplet digital RT-PCR. The study demonstrated the enrichment of HPV16 DNA in the exosomes isolated from the saliva of HPV-OPC patients suggesting their putative application in saliva exosome-based liquid biopsies (143). In their review article, Nonaka and Wong have discussed in detail the current status of salivary exosomes and their molecular content in the context of developing diagnostic and prognostic biomarkers and developing saliva exosomes as a novel modality of liquid biopsies.…”
Section: Phasementioning
confidence: 99%